Pengaruh Bahan Ajar IPA Terpadu Tema Kesehatan Pernapasan dan Ekskresi Bermuatan Literasi Era Digital Terhadap Kompetensi Siswa Kelas VIII SMPN 15 Padang - Kartika Adrianti; Asrizal Asrizal; Amali Putra (Universitas Negeri Padang, 2018)
Literation is needed in facing of 21 st century challengers. To face this challenge The Government of Indonesia encourages the literacy movement at school, which is abbreviated with GLS. The real condition show that science learning is still now well implemented, and student literacy is still slow. The solution of the problem is applying integrated science to charged literacy of the digital age. The objective of the research is to determine the effect of integrated teaching materials on the theme respiration health and exretion of digital literacy on the competence of students of class VIII SMPN 15 Padang.The tipe of reasearch conducted is quasi experimental. The research designed used was a nonequivalent control gruop with posttest only. The population of this study is all students of class VIII registered in semester 1 academic year 2017/2018 SMPN 15 Padang.. This study uses two sample classes. The sample class students are 64 students. This sample class is chosen by combining purposive sampling technique and random cluster sampling. The research instrument is a written test sheet for the knowledge aspect, an observation sheet for the attitude aspect, and a performance assesment sheet for the skill aspect. Research date were analyzed by using descriptive analysis and equality test of two averages.From the data analysis, it can be found that the application of science an integrated teaching materials of the theme of respiratory and excavated health to the knowledge, attitude, and skill aspect of the students of grade VIII SMPN 15 Padang at the real level of 95%. A positive influence on the use of integrated science materials can improve aspects of knowledge, attitudes, and skills. Thus an integrated science teaching material of respiratory and excavated healthcare excretion of the digital era is well used for integrated science learning.